"We just eat this food because of hunger or because we cannot afford other foods": Drivers of Adolescent Food Choice From the Perspectives of Adolescents and Influential Adults. (14th June 2022) - Seiger, Emily; Ouda, Rosebel; Ruto, Nathan; Dianga, Peter; Lytle, Leslie; Meyer, Katie; Ammerman, Alice; Voruganti, Saroja; Nandoya, Erick; Omala, Hillary; Owuor, Mercy; Martin, Stephanie
Abstract: Objectives: Kenya is experiencing rapid urbanization with increasing access to processed food and high rates of stunting, micronutrient deficiencies, and overweight/obesity. Rates of overweight and obesity are highest among women in urban areas, but evidence is limited in adolescence, a critical time for habit formation. This study aimed to understand the factors that influence adolescent girls' food choices. Methods: We conducted interviews and free-listing with influential adults (parents and food vendors, n = 7) and adolescent girls (n = 4), and three focus group discussions (FGDs) with pile sorts with 15–19 year old girls (8–11 girls per group) living in Kibera. Participants were purposively sampled. FGDs and interviews were audio recorded, transcribed and translated, and analyzed thematically. Analysts in Kenya and the US coded transcripts using Atlas.ti 9 and met regularly to discuss themes. Results: Focus group participants had a mean age of 17.8 years and included girls who were in school, out of school, and working. Participants lived in 10 of 13 villages in Kibera. Across interviews and FGDs, participants described affordability being the primary influence of food choice in Kibera. Influential adults identified that adolescents are most likely to eat foods like chips and sweets compared to adults. Bean and corn stew (githeri), sweet and Irish potatoes, tea without milk, porridge, leafy greens (sukuma wiki), and rice were considered affordable and commonly consumed in Kibera. Tea with milk, stiff maize porridge (ugali), kidney beans (njahe), dairy foods, sweets, and soda were only consumed if families have money. Participants reported it was common to skip meals (typically lunch) to save money for the other meals. During pile sort activities, adolescents demonstrated knowledge of healthy and unhealthy foods. Many adolescents discussed how affordability, foods offered at school, family circumstances, relationships with food vendors, preferences, and peer-pressure influence what they eat. Conclusions: Adolescent girls had general knowledge and interest in eating healthy foods, but factors like affordability, place of consumption, and family influence dominate food choices. Adolescents must be involved in the design of interventions to improve their diets. Funding Sources: UNC Chapel Hill Nutrition Dept. Pilot Grant.